Spółdzielczość walczy o trwały pokój między narodami. (Gdynia : [s.n.], 1948)
Afisz z programem obchodów Dnia Spółdzielczości w Gdyni 3.07.1948 r.
Keywords: Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- plakaty; Gdynia (Polska) -- 1945-1970 -- źródła